2004
DOI: 10.1124/dmd.104.001917
|View full text |Cite
|
Sign up to set email alerts
|

LACK OF EVIDENCE FOR INDUCTION OF CYP2B1, CYP3A23, AND CYP1A2 GENE EXPRESSION BY Panax ginseng AND Panax quinquefolius EXTRACTS IN ADULT RATS AND PRIMARY CULTURES OF RAT HEPATOCYTES

Abstract: ABSTRACT:Treatment of rats with a single oral dose (10-30 mg/kg) of a crude Panax ginseng extract of unknown ginsenoside content has been reported to modestly increase hepatic microsomal cytochrome P450-mediated aminopyrine N-demethylation activity. In the present study, we compared the effect of P. ginseng and Panax quinquefolius extracts on rat hepatic CYP2B1, CYP3A23, and CYP1A2 gene expression. Adult male Sprague-Dawley rats (250-275 g) received, by oral gavage or i.p., P. ginseng extract [4% (w/w) total g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…When Yu et al compared the effect of American ginseng and Asian ginseng extracts on gene expression of the hepatic P450 enzyme in adult rats and primary cultures or rat hepatocytes, there was no evidence of the induction of CYP2B1, CYP3A23, or CYP1A2 cultures of rat [47]. In another study ginseng had no effect on a number of CYP isoforms, including CYP3A4, CYP1A2, CYP2E1 and CYP2D6 [48, 49].…”
Section: Potential Ginseng-drug Interactionsmentioning
confidence: 99%
“…When Yu et al compared the effect of American ginseng and Asian ginseng extracts on gene expression of the hepatic P450 enzyme in adult rats and primary cultures or rat hepatocytes, there was no evidence of the induction of CYP2B1, CYP3A23, or CYP1A2 cultures of rat [47]. In another study ginseng had no effect on a number of CYP isoforms, including CYP3A4, CYP1A2, CYP2E1 and CYP2D6 [48, 49].…”
Section: Potential Ginseng-drug Interactionsmentioning
confidence: 99%
“…Liu et al found that PPT and PPD, the deglycosylation products of naturally occurring ginsenosides, exhibited potent inhibition against CYP3A4 activity, and compound K and ginsenoside Rh2, which are more concentrated in fermented red ginseng than in red ginseng or fresh ginseng, also exhibited moderate inhibition of CYP2C9 and CYP3A4 activity . Moreover, many in vitro studies have supported the idea that the ginsenosides, including ginsenoside Rb1, Rb2, Rc and Rg1, in fresh ginseng do not affect CYP enzyme activity but that metabolites of these inhibit CYP1A2, CYP2C9 and CYP3A4 . However, in this study, oral administration of fermented red ginseng inhibited CYP1A2 enzyme activity, but this effect is unlikely to cause significant interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Yu et al compared the effects of American ginseng ( Panax quinquefolius ) and Asian ginseng ( Panax ginseng ) extracts on gene expression of the hepatic P450 enzyme in adult rats and primary cultures or rat hepatocytes . They found no evidence of the induction of CYP2B1, CYP3A23 or CYP1A2 in rat cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Our results imply a possible clinical interaction between the two drugs, but should be eventually confirmed in an in vivo study. In a recent study performed after oral administration of G115 extract to rats, it was shown that it does not induce CYP2B1,CYP3A23 or CYP1A2 (P450 isoenzymes) gene expression (Yu et al, 2005). Interaction studies are of major importance since herbal remedies are sold without prescription and often used without the knowledge of the patient's physician.…”
Section: Discussionmentioning
confidence: 98%